2012
DOI: 10.1080/13698575.2012.697130
|View full text |Cite
|
Sign up to set email alerts
|

Accentuate the positive, eliminate the negative? The variable value dynamics of non-suicidal self-hurting

Abstract: Medical accounts mostly frame non-suicidal self-hurting as an adverse event, the frequency of which has supposedly increased to a current 'epidemic' level, and which can be predicted probabilistically in terms of risk factors. This set of presuppositions gives rise to the common stigmatisation of those who present to Accident and Emergency services as a result of self-hurting. It is now being challenged in a small but growing body of social science literature which emphasises the diversity of self-hurting, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…For example, Adshead (2010) takes a more psycho-analytical approach and argues that self-harm can be read as a form of communication which is used to express self-hatred and rage. Similarly, Klonsky (2009) and Barton-Breck and Heyman (2012) concluded that participants’ reasons for self-harm involved affect regulation, the need for emotional release and self-punishment, and Chandler (2014) highlighted a key role for regaining control. Similarly, Long et al (2013) emphasised the psychological damage caused by life events and trauma, and in a large-scale quantitative study, the most commonly cited reasons for self-harm were ‘feeling the body is real’, ‘getting rid of anger’, ‘stopping guilt’ and ‘distraction from memories’ (Briere and Gil, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Adshead (2010) takes a more psycho-analytical approach and argues that self-harm can be read as a form of communication which is used to express self-hatred and rage. Similarly, Klonsky (2009) and Barton-Breck and Heyman (2012) concluded that participants’ reasons for self-harm involved affect regulation, the need for emotional release and self-punishment, and Chandler (2014) highlighted a key role for regaining control. Similarly, Long et al (2013) emphasised the psychological damage caused by life events and trauma, and in a large-scale quantitative study, the most commonly cited reasons for self-harm were ‘feeling the body is real’, ‘getting rid of anger’, ‘stopping guilt’ and ‘distraction from memories’ (Briere and Gil, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Self-harm may also be triggered by adult experiences, and research indicates that traumatic experiences such as rape or assault can also increase the likelihood of an individual engaging in self-harming behaviours in later life (Long et al, 2013). In contrast, some studies have called for a move away from risk and aetiological factors towards an emphasis on reasons and the individual’s own perspective (Barton-Breck and Heyman, 2012; Chandler, 2014; Harris, 2000). For example, Adshead (2010) takes a more psycho-analytical approach and argues that self-harm can be read as a form of communication which is used to express self-hatred and rage.…”
Section: Introductionmentioning
confidence: 99%
“…In consequence, one way to protect a valued activity from the charge of irresponsible risk-taking is to differentiate safe and dangerous sub-categories. This socio-cognitive manoeuvre will be documented in the present special issue in relation to illicit drug consumption (Caiata-Zufferey, 2012) and self-hurting (Barton-Breck and Heyman, 2012). Similarly, choices about time-framing and time-discounting can be used to change the value of an outcome, for instance if the effectiveness of an intervention is only considered over a short period so that relapses occur beyond the observer-set temporal horizon.…”
Section: Values and Health Risks: An Editorialmentioning
confidence: 99%
“…Patients may, on average, overestimate the adversity of subsequently living with a permanent stoma (Bossema et al, 2007), and some of the early problems appear to be experienced as less adverse after a year of usage (Grumann et al, 2001). This analysis represents social actors as passive experiencers of value, but individuals may attempt to actively mitigate risks, as illustrated by Barton-Breck and Heyman (2012) in this volume, a possibility which renders static cost-benefit analyses more or less useless.…”
Section: The Problem Of Multiple Consequencesmentioning
confidence: 99%
“…In relation, secondly, to the often taken-for-granted negative value judgements through which adversity is projected onto 'event' categories, giving them an aura of intrinsic 'adversity', the published papers covered: recreational heroin and cocaine consumer perspectives on safe and risky usage (Caiata-Zufferey, 2012); the benefits and costs of non-injurious self-harming (Barton-Breck and Heyman, 2012); the prioritisation of protecting the public versus reintegration into the community as viewed by discharged forensic mental health service users (Coffey, 2012); a case study of a woman whose action choice put her recovery from anal cancer at serious risk (Heyman, McGrath, Nastro, Lunniss and Davies, 2012); and the value judgements made by pregnant teenagers about their condition (Hoggart, 2012). One theme runs clearly through this work: that individuals frequently challenge the projected medical and societal value judgements which underlie risk-thinking.…”
Section: The 'Lens Of Risk' Special Issue Seriesmentioning
confidence: 99%